Blow Up: after that image (ModaPalavra e-periódico, 2008)
Antonionni’s Blow Up is one of those movies that, besides outdated, do not miss its modern fresh. This article pays attention to questions that, as I understand, are especially important when considering our modern days: image, media and fashion. These themes are here discussed in a very particular way, emphasizing the matters related to image.